Pengkajian Permohonan Izin Terbang (Flight Approval) Untuk Penambahan Penerbangan (Extra Flightj Rute Dalam Negeri di Bandar Udara Ngurah Rai - Bali - Yuliana, Dina (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2011)
Research about Flight Approval for Extra Flight Domestic Route in the Ngurah Rai Airport Bali has been done. The aim of research is to kncnv the difference of the perception behveen the airlines for the mechanism of the implementation flight approval to extra flight in the Ngurah Rai Airport - Bali by the Director General of Aviation Transportation by using the Kruskal Wallis Test method. The results of the research show that there are significant difference perception bet-ween the airlines, but in the principle perception of airline was together positive tawards the process of flight approval in hard copy (physical) was compared through the short message service, the facsimile or the electronics letter (the e-mail/g-mail). As long as period in September 2010 up to March 2011 (7 months), total flight approval to extra flight was 685 and it was increased on the day or the holiday season like at the time of the New Year holiday (in December - in January) and the school child's holiday (in May - in June) on 2010. Keywords: flight approval, extra flight, Kruskal Wallis Test, airlines